Searching for the "lost links": settlement project and identification ways amongst settled rural workers (Cadernos de Psicologia Social do Trabalho, 2009)
In view of the transformations of the rural labor world, the organization of rural settlements based on agro-ecology and associativism surges as a possibility to ensure the social reproduction of rural workers. What are the ways those individuals follow when designing their lives, trying to meet the requirements of settlement projects as well as survival needs? This article discusses that issue, starting from a specific assumption: understanding the reasons, criteria and values which informed the workers about the organizational structure configuration - the formation of groups of workers - at the moment of legal constitution of a determinate settlement. By understanding identity as a preparation process and by cross-checking information obtained through document analysis, and carrying out direct observations and collective and individual interviews, I analyzed the dynamics of the nucleation process considering the characteristics of the settlement project as well as the settled rural workers', and trying to understand the existence of probable relations with the meanings attributed to cooperation by the workers.